Biomechanical analysis of topspin techniques in table tennis games - Aulia Gusdernawati; Widiyanto Widiyanto; Ahmad Nasrulloh (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2021)
Motion analysis in sports can help athletes and coaches as material for evaluating movement in improving movement and improving athlete performance with a predetermined training program. The purpose of this study was to analyze the motion of the topspin technique in table tennis. This research is a qualitative research by describing the results of the video analysis of the topspin technique movement which is accessed from youtube, then using the Kinovea application instrument. The subjects in this study were the top ranked players, which consisted of five of the best male athletes at the world level in the table tennis game. Based on the analysis data above, it was found that the average bending of the elbow at the ready position was 92.80, the swing position before hitting the ball was 142.40, when hitting the ball was 117.80, and after hitting the ball was 73.40. The results of the average elbow distance from the center point when the ready position is 68.728 cm, when the swing position before hitting the ball is 23.532 cm, when hitting the ball with a distance of 50.88 cm and during further motion 150.768 cm. The results of the analysis of the inclination angle of the body when the ready position is 161.60, when swinging the hand 152.60, when hitting the ball 150.60, and for further motion with a body inclination of 1660. The results of the analysis of the bending of the right leg when the position is 149.80, the position of swinging the right leg 125.40, and when the ball hits it forms an angle of 125.60 and when it continues to move 42.60. The average results of the analysis of the left leg bending angle when the ready position is 151.20, the swinging position with the left leg bending is 126.20, in the position of the ball hitting an angle of 130.40, and accompanied by a follow-up motion to form the left foot angle of 1460. The average foot distance when hitting the topspin, in the ready position is 186 cm, during the backswing the foot distance is 196.638 cm, and when hitting the ball is 198.81 cm, and accompanied by a follow-up motion of 195.886 cm. Biomechanical analysis of the topspin technique from several stages starting from the ready position to the advanced motion carried out by each athlete according to their respective body anatomy and following the position when hitting the ball.Analisis biomekanika teknik topspin pada permainan tenis mejaAbstrakAnalisis gerak pada olahraga dapat membantu atlet dan pelatih sebagai bahan evaluasi gerakan dalam memperbaiki gerakan dan meningkatkan performa atlet dengan program latihan yang telah ditentukan. Tujuan penelitian ini ialah menganalisis gerak teknik topspin dalam permainan tenis meja. Penelitian ini merupakan penelitian kualitatif dengan mendeskripsikan hasil analisis video gerakan teknik topspin yang diakses dari youtube, kemudian menggunakan instrumen aplikasi Kinovea. Subyek dalam penelitian ini men top ranked players yang berjumlah lima orang atlet putra terbaik ditingkat dunia pada permainan tenis meja. Berdasarkan dari data analisis diatas ditemukan nilai rerata tekukan siku pada saat posisi siap 92,80, posisi ayunan sebelum memukul bola 142,40, saat memukul bola 117,80, dan sesudah memukul bola sebesar 73,40. Hasil rerata jarak siku dari titik pusat saat posisi siap 68,728 cm, saat posisi ayunan sebelum memukul bola 23,532 cm, saat memukul bola dengan jarak 50,88 cm dan saat gerak lanjutan 150,768 cm. Hasil analisis sudut kecondongan tubuh saat posisi siap 161,60, saat mengayunkan tangan 152,60, saat memukul bola 150,60, dan untuk gerak lanjutan dengan kecondongan tubuh 1660. Hasil analisis tekukan kaki kanan saat posisi 149,80, posisi mengayunkan kaki kanan 125,40, dan saat perkenaan bola membentuk sudut 125,60 dan saat gerak lanjutan 42,60. Hasil rerata analisis sudut tekukan kaki kiri saat posisi siap 151,20, posisi mengayungkan tangan dengan tekukan kaki kiri 126,20, pada posisis perkenaan bola membentuk sudut 130,40, serta diiringi dengan gerak lanjutan membentuk sudut kaki kiri 1460. Hasil rerata jarak kaki saat melakukan pukulan topspin, pada posisi siap 186cm, saat backswing jarak kaki 196,638 cm, dan saat perkenaan bola 198,81 cm, serta di iringi gerak lanjutan 195,886 cm. Analisis biomekanik teknik topspin dari beberapa tahapan dimulai dari posisi siap hingga gerak lanjutan yang dilakukan masing-masing atlet sesuai anatomi tubuh masing-masing serta mengikuti posisi saat perkenaan bola.